2013
DOI: 10.1007/s12665-013-2861-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural and artificial radioactivity levels and hazards of soils in the Kücük Menderes Basin, Turkey

Abstract: In this study, natural and artificial radionuclide activity concentrations in surface soils of Kücük Menderes Basin have been measured using gamma spectroscopy. The soil samples were collected from agricultural lands in the Kücük Menderes Basin in Turkey. The activity concentrations of 226 Ra, 232 Th, 40 K and 137 Cs in the soils were found to be range of 12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The specific activities for 226 Ra were evaluated from the three γ-ray lines obtained from photopeaks 214 Bi (609.3 keV (44.8%), 1120 keV (15.1%) and 1764.5 keV (15.8%)), while specific activities of 232 Th were calculated from the average value of the two γ-ray lines obtained from the pho-Adsorbed dose rate and contribution of 226 Ra, 232 Th and 40 K to absorbed dose rate Absorbed dose rate in air (D a ) usually expresses the health effects of γ-ray radiation from the natural radioactive sources in the environment. D a values at the high 1 m above the ground were calculated fromthe measured specific activities of 226 Ra, 232 Th, and 40 K by using the following23,24) equation(3),…”
mentioning
confidence: 99%
“…The specific activities for 226 Ra were evaluated from the three γ-ray lines obtained from photopeaks 214 Bi (609.3 keV (44.8%), 1120 keV (15.1%) and 1764.5 keV (15.8%)), while specific activities of 232 Th were calculated from the average value of the two γ-ray lines obtained from the pho-Adsorbed dose rate and contribution of 226 Ra, 232 Th and 40 K to absorbed dose rate Absorbed dose rate in air (D a ) usually expresses the health effects of γ-ray radiation from the natural radioactive sources in the environment. D a values at the high 1 m above the ground were calculated fromthe measured specific activities of 226 Ra, 232 Th, and 40 K by using the following23,24) equation(3),…”
mentioning
confidence: 99%
“…In this study, the activity concentration in most soil samples was found to be higher than in the study conducted in 2020. In Küçük Menderes Basin-Turkey, the activity concentrations were found to be in the range of 12.63 -72.51 ( 26 Ra), 11.45 -58.12 ( 232 Th), 234.8 -1058.52 ( 40 K), 2.31 -7.75 ( 137 Cs) Bq kg −1 [29]. In Bolu-Turkey, the activity concentrations of 226 Ra, 232 Th, 40 K, and 137 Cs in soil samples were found to be 3.8-49.9, 4.1-37.9, 64.6-518.9, and 0.6-43.6 Bq kg −1 , respectively [30].…”
Section: Resultsmentioning
confidence: 99%
“…Radyasyon doz hesaplarında bölgeye ait doğal kaynaklar ve bu kaynakları oluşturan radyonüklidlerin çevredeki konsantrasyonlarının ve radyasyonun özellikle insanda olmak üzere, biyolojik sistemler üzerindeki etkisini belirlemek amacıyla dünyada ve Türkiye'de birçok çalışma yapılmaktadır [6][7][8][9]. Bu çalışmada, Edirne ve Kırklareli illeri arasındaki otoyol boyunca toplanan toprak örneklerinde 226 Ra, 232 Th ve 40 K doğal radyonüklid konsantrasyonları gama spektrometresi ile ölçülmüştür.…”
Section: Introductionunclassified